اللغــة الشعرية - ناصر بشير مطيع; داود غيثاء حبيب (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
يسعى البحث في اللغة الشعرية إلى تبيان خصيصات هذا الاصطلاح المعاصر، بعد أن يبين أبعاده التاريخية. ويركز البحث في المقام الأول على الخلفية اللغوية والاصطلاحية، لما يثيره هذا الاصطلاح من مواقف متباينة في الخطاب النقدي المعاصر. وقد خلصنا إلى أن للشعرية بذوراً في الموقف النقدي العربي القديم، بيد أنه يحتاج إلى تطوير وتعميق، كي يحقق ألق الحضور والمواظبة. Studying poetically language aims to show the characteristics of this modern term revealing its historical dimensions. This research focuses –in the first place- on the linguistic and terminological background, because this term has resulted in different attitudes in the modern critical discourse. And we have concluded that poetically has many seeds in the past Arabic criticism, but it needs to be developed and deepened to achieve the glamour of presence and progress.